1977
DOI: 10.1085/jgp.70.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Pig reticulocytes. III. Glucose permeability in naturally occurring reticulocytes and red cells from newborn piglets.

Abstract: The loss of facilitated glucose transport of red cells occurring in the newborn pig was monitored in 11 density-separated cells from birth to a 4 wk of age. At birth there was a threefold increase in glucose permeability from the lightest cells to the most dense, suggesting that cells having progressively less glucose permeability are released into the circulation as gestation proceeds. Because of extraordinary stimulation of erythropoietic activity, the uppermost top fraction constituting 2-3 percent of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The decrease in membrane permeability to glucose seen in reticulocytes undergoing maturation confirms and corroborates the results suggested by the earlier work of Kim and Luthra (1977). In the newborn pig, the reticulocytes present at birth still possess a small but well-defined permeability to glucose.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The decrease in membrane permeability to glucose seen in reticulocytes undergoing maturation confirms and corroborates the results suggested by the earlier work of Kim and Luthra (1977). In the newborn pig, the reticulocytes present at birth still possess a small but well-defined permeability to glucose.…”
Section: Discussionsupporting
confidence: 89%
“…However, an impressive latent glycolytic capacity can be demonstrated either in the adult pig cells rendered pervious to glucose by treatment with a polene antibiotic, amphotericin B (Kim and McMannus, 1971 a,b) or in the postnatal cells which have a high glucose permeability, exhibiting carrier-mediated transport (Kim et al, 1971;Zeidler et al, 1976). Moreover, a transitory glucose permeability with a concomitant glycolysis takes place both in the experimentally induced reticulocytes of the adult animal (Kim et al, 1976 a,b) and in the naturally occurring reticulocytes of the postnatal piglets (Kim and Luthra, 1977). The results emerging from this laboratory indicated that the membrane permeability to glucose is quickly lost in the course of normal maturation of reticulocytes to erythrocytes in vivo (Kim et al, 1976 a,b;Kim and Luthra, 1977).…”
mentioning
confidence: 99%
“…Kim & Luthra (1977) using density separation and 5l0r and 59Fe labelling techniques suggested that the loss of transport activity in the pig after birth resulted from the replacement of glucose-permeable cells with glucose-impermeable erythrocytes. Unlike the pig, the sheep possesses a distinct fetal haemoglobin, and in the present series of experiments it was possible to compare directly the changes in the two parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The reticulocytes were stained with new methylene blue dye (Sigma Chemical Co., St. Louis, Mo.) as described elsewhere (Kim and Luthra, 1977).…”
Section: Anemic Stressmentioning
confidence: 99%